Kerusakan Pucuk Tebu oleh Scirpophaga nivella (F.) di Pertanaman Tebu Lahan Kering, PTPN VII Cinta Manis - Dewi Meidalima; Ruarita Ramadhalina Kawaty (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
The biggest obstacle sugarcane in Indonesia, including in South Sumatra and centers Cinta Manis sugar cane plantations that attack shoot borer (Scirpophaga nivella (F.). The study was conducted from July to December 2012 in PTPN VII Cinta Manis South Sumatera. One ha land observation area. Observation plots were divided into 5 plot diagonally into 5 plots each measuring 200 m2 with a population of approximately 1500 sugarcane stalks, performed every 2 weeks old plants of 1.5 months to 6.5 months. The research purposes were observing damage of sugarcane shoots by shoot borer (Scirpophaga nivella). Experimental research methods, data were collected purposively and directly at the affected plants. Hoist length formed by shoot borers from leaves to growing points was the 18.47 cm. Place of imago out mostly on the 3rd and 4th segment. Length of drilled stem was 8.20 cm. Damage caused by shoot borer could made totally dead or made siwilan on sugarcane.